Development of Gamification-Based Wayground Learning Media on Geographical Conditions Material in Junior High School - Ibrahim, Jodi Sadam; Fauziah, Vera Sophia (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2025)
Geography instruction at the Junior High School (SMP) level often encounters obstacles regarding low student interest and comprehension due to material presentations that tend to be abstract and monotonous. This research aims to develop and test the effectiveness of